Disparity in Access and Poorer Health Status in Non-Majority Populations - Fralinger, David (Journal of the Pediatric Orthopaedic Society of North America, 2023)
North America is a large, diverse continent, which has a longstanding history of inequality for its diverse population. These historical inequalities continue to impact health outcomes and access to healthcare of non-majority groups. To ensure the best healthcare outcomes for patients, pediatric orthopaedic surgeons must be aware of these inequities in order to combat them and minimize their effects.